👤

Calculati :
a) ( 10^2 - 8^2 ) : 6 : 2 + 1^2003 ;
b) ( 3^32 : 3^2 + 2^2 * 2^25 - 2003^0 ) : ( 27^10 + 8^9 - 324 : 18^2 )


Răspuns :

a) [tex]( 10 ^{2} ^ - 8^{2 }) : 6 : 2 + 1^{2003 }=(100-64):6:2+1=36:6:2+1[/tex]=[tex]6:2+1=3+1=4[/tex]
b) [tex]( 3^{32} : 3^{2}+ 2^{2}* 2^{25} - 2003^{0}) : ( 27^{10} + 8^{9} - 324 : 18^{2})[/tex]=[tex]( 3^{32-2} + 2^{2+25} - 1) : [(3 ^{3}) ^{10} + (2^{3} )^{9} - 18^{2} : 18^{2}][/tex]=[tex]( 3^{30} + 2^{27} - 1) : [(3 ^{3*10}) + (2^{3} )^{9} - 18^{2-2}]=[/tex][tex]( 3^{30} + 2^{27} - 1) : (3 ^{30} + 2^{3*9} - 18^{0})=( 3^{30} + 2^{27} - 1) : (3 ^{30} + 2^{27} - 1)=[/tex][tex]1[/tex]